Effect of information and communication technology-based loyalty incentives on farmers’ use of agricultural inputs and soybean yields: evidence from a field experiment in Uganda - Ayesiga, Connetie; Ronner, Esther; Ebanyat, Peter; Giller, Ken E.; Ingenbleek, Paul T. M. (Taylor & Francis group, 2025)
To address low yields and contribute to food security in sub-Saharan Africa, policy-makers encourage smallholders to use productivity-enhancing agricultural inputs such as improved seed varieties, fertilisers and inoculants. However, adoption rates among smallholders remain low, partly because farmers are uncertain whether buyers will reliably purchase their higher-quality outputs at premium prices. Loyalty incentives simultaneously encourage input use and signal buyer commitment, which may help reduce this uncertainty. Using survey data from a cluster-randomized field experiment involving 234 soybean farmers in Northern Uganda, this study examines the effects of loyalty incentives delivered viaan Information and Communication Technology (ICT) platform on farmers' use of agricultural inputs and soybean yields. The findings show that both financial and non-financial loyalty incentives significantly (p < 0.001) increasedofarmers’ use of improved seed and fertiliser compared with no incentives. Correspondingly, soybean yields significantly increased above the control group mean (619 kg ha−1), with increases of 525kg ha−1 for non-financial incentives, 747 kg ha−1 for financial incentives, and 854 kg ha−1 for combined incentives. Overall, the results demonstrate that loyalty incentives caneffectively promote the adoption of productivity-enhancing inputs and increase yields in smallholder systems, contributing to sustainable agricultural intensification and advancing understanding of a technology adoption through ICT-enabled interventions.
Keywords: ICT platforms; ICT4D; outputmarket access; technologyadoption; producer-buyerrelationship; sub-SaharanAfrica